2020
DOI: 10.1002/suco.202000119
|View full text |Cite
|
Sign up to set email alerts
|

The influence of aging on the fracture characteristics of recycled aggregate concrete through three methods

Abstract: In this research, to assess the impact of aging on the fracture properties of recycled aggregate concrete (RAC), three‐point bending tests were carried out on 260 specimens. Then, work of fracture method (WFM), size effect method (SEM), and boundary effect method (BEM) were utilized for analysis of fracture parameters. The result showed that fracture energy values for RAC were 4.2%, 7.1%, 22.7% and 24.2% less than natural aggregate concrete (NAC) ones at 3, 7, 28 and 90 days, respectively. Based on calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In addition to the destruction of natural resources, it imposes a lot of solid waste in the environment. 19,29,32,33,38,39,42,56,62 Abbreviations: AC, curing age; ADR, additive regression; B, total binder; BAG, bagging predictors; CA, coarse aggregate; CS, compressive strength; DT, decision table; GF, glass fiber; GPR, Gaussian process regression; LWL, locally weighted linear; M5R, M5-Rules; MLP, multilayer perceptron; RA, recycled aggregates; RAC, recycled aggregate concrete; REPT, reduced-error pruning tree; RF, random forest; SF, silica-fume; SSD, saturated surface dried; SVR, support vector regression; W, water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the destruction of natural resources, it imposes a lot of solid waste in the environment. 19,29,32,33,38,39,42,56,62 Abbreviations: AC, curing age; ADR, additive regression; B, total binder; BAG, bagging predictors; CA, coarse aggregate; CS, compressive strength; DT, decision table; GF, glass fiber; GPR, Gaussian process regression; LWL, locally weighted linear; M5R, M5-Rules; MLP, multilayer perceptron; RA, recycled aggregates; RAC, recycled aggregate concrete; REPT, reduced-error pruning tree; RF, random forest; SF, silica-fume; SSD, saturated surface dried; SVR, support vector regression; W, water.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the solid waste of countries is usually caused by construction and demolition in the construction industry. In addition to the destruction of natural resources, it imposes a lot of solid waste in the environment 19,29,32,33,38,39,42,56,62 …”
Section: Introductionmentioning
confidence: 99%
“…Concrete is a synthetic material that varies significantly in mechanical characteristics during its manufacturing. The fracture behaviors of concrete are influenced by its age, and the fracture toughness at different ages t is assessed by KICKIC28=m()t28n, where KIC28 is KIC at 28 days, m and n mean the dimensionless constants, which are m=1, n=0.1307 in the literature, 60 and m=0.65, n=0.1297 in the literature 61 . As illustrated in Figure 16B, it is observed that the fracture load envelope enlarges with the age of concrete.…”
Section: Fracture Criteria Of Concretementioning
confidence: 99%
“…where K IC28 is K IC at 28 days, m and n mean the dimensionless constants, which are m ¼ 1, n ¼ 0:1307 in the literature, 60 and m ¼ 0:65, n ¼ 0:1297 in the literature. 61 As illustrated in Figure 16B, it is observed that the fracture load envelope enlarges with the age of concrete.…”
Section: Fracture Criteria Of Concretementioning
confidence: 99%
“…In the case of the test method to investigate the fracture characteristics, various test methods have been applied according to the research purpose and the characteristic of the material. reepoint bending test is commonly used to investigate the mode I fracture characteristics of material such as concrete [18,19]. Based on the test results, stress intensity factor and fracture energy were calculated to investigate effects of fines and temperature on the fracture characteristics of frozen sand.…”
Section: Research Significancementioning
confidence: 99%